PENGELOLAAN DAUR ULANG SAMPAH PLASTIK DI KAWASAN WISATA PANTAI PANYURAN KABUPATEN TUBAN UNTUK MENINGKATKAN NILAI JUAL SAMPAH DENGAN PERAN SERTA MASYARAKAT - Maulita Mega Kusumawati; Naniek Ratni J.A.R (EnviroUS, 2021)
ABSTRACT Panyuran beach is a very famous tourist destination in the Tuban area is an average number of tourists in the last 3 months, from August to October 2020, is 25,199 people. The research time had been carried out for 14 days in the Panyuran beach.tourism area using the data collection method, namely the Simple Random Sampling method. The results obtained are 400 kg of total waste generation and divided into 25 kg of paper waste, 66 kg of organic waste, 10 kg of non-organic waste, and 299 kg of plastic waste. For plastic waste that is suitable for recycling, which is 299 kg, and the remaining 101 kg is waste other than plastic waste which will be forwarded to the TPS.